Empreendedorismo cultural em Camaçari/BA: relatório de análise e orientações para a formulação de políticas públicas pautadas na indústria criativa - Oliveira, Halisson Deivid de Jesus (2024)
This technical report is the result of a study carried out in the professional master's degree in Public Administration and presents an analysis of the problem situation, related to cultural entrepreneurship in the municipality of Camaçari/BA, with essence in the potential for creating public policies based on the creative industry. The intervention proposal aims to strengthen the local economy by promoting cultural entrepreneurship, identifying challenges and opportunities, in addition to suggesting action strategies for local public administration. Practical contributions include promoting innovation, sustainability of creative industries, generating jobs and income, and valuing cultural diversity in the municipality. This technical report serves as a guiding and decision-making instrument so that political agents can apply measures that provide diversification of the municipality's economic matrix.